2022
DOI: 10.1038/s41598-022-12373-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of invasive versus native whitefly species and their pyrethroid knock-down resistance allele in a context of interspecific hybridization

Abstract: The invasion success of a species in an agrosystem is greatly influenced by environmental factors such as the use of insecticides, by the intrinsic evolutionary capabilities of the species, and also by interactions with resident species. On the island of La Réunion, the successive invasions of MEAM1 and MED whitefly species over the last 20 years have not only led an increased use of insecticides, but have also challenged the resident IO species. To trace the evolution of the 3 species, and the distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…The same screening was performed for the MED Q1 individuals, and within these individuals 3/46 were found with an assignment to the MED ASL genetic cluster. The mtCOI haplotype (maternally transmitted) gives the direction of the initial cross for hybrids: a MED ASL mtCOI haplotype indicates a cross between a MED ASL female and a MED Q1 male (and vice versa) [ 35 ]. Consequently, we identified slightly more interspecific matings with MED ASL females than with MED Q1 females (10% versus 6%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same screening was performed for the MED Q1 individuals, and within these individuals 3/46 were found with an assignment to the MED ASL genetic cluster. The mtCOI haplotype (maternally transmitted) gives the direction of the initial cross for hybrids: a MED ASL mtCOI haplotype indicates a cross between a MED ASL female and a MED Q1 male (and vice versa) [ 35 ]. Consequently, we identified slightly more interspecific matings with MED ASL females than with MED Q1 females (10% versus 6%).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been shown that the B . tabaci IO species, indigenous of the Indian ocean islands, was highly susceptible to insecticide compared to the invasive MEAM1 species and allowed MEAM1 to be dominant in crops, particularly in areas where phytosanitary pressure is high [ 35 , 46 ]. Similarly, comparative studies of life history traits of populations of MED ASL and MED Q1 in Côte d’Ivoire could also provide a better understanding of their distributions and the interactions between these species.…”
Section: Discussionmentioning
confidence: 99%